2019
DOI: 10.1016/j.jaip.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Versus Actual Aeroallergen Sensitization in Urban Children

Abstract: Background: Individuals often report allergy to specific aeroallergens, but allergy testing can reveal disparate sensitization.Objective: To characterize the agreement between perceived and actual sensitization to individual aeroallergens in an urban pediatric population.Methods: 253 children were enrolled from pediatric clinics in New York, NY. Detailed questionnaires regarding perceived sensitization and serum specific IgE measurements to ten common aeroallergens were completed. Agreement between perceived a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…[ 5 ] 63.6% children enrolled from pediatric clinics in New York reported perceived sensitization to one or more aeroallergen, with cat dander and dust being the most sensitive. [ 20 ] In this study, we find that 59.70% children enrolled from West China Second University Hospital were allergic to at least 1 allergen. One child may be allergic to different allergens.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…[ 5 ] 63.6% children enrolled from pediatric clinics in New York reported perceived sensitization to one or more aeroallergen, with cat dander and dust being the most sensitive. [ 20 ] In this study, we find that 59.70% children enrolled from West China Second University Hospital were allergic to at least 1 allergen. One child may be allergic to different allergens.…”
Section: Discussionmentioning
confidence: 74%
“…[ 25 ] Another study in New York revealed that tree pollen is the most commonly reported aeroallergen of children followed by dust. [ 20 ] In our study, we find that milk, egg, house dust mite, dust mite, and dust are the most common allergens among children in the Sichuan province. Accumulated studies found that most food reactions occur during the first year of life.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, of those children who denied any perceived sensitization the type of allergen with highest actual sensitization rate were pet dander(34.3%), followed by molds(18.1%), and cockroach(12.6%). A US study of 253 urban children had reported similar finding that even if a child does not perceive sensitization to any allergen, actual allergen sensitization is still possible, particularly for indoor allergens cockroach [12]. In addition, Li JT et al study had previously examine the ability of allergic patients to correctly predict SPT results, showing that only 10 to 56% of predictions for skin test result were correct [13].…”
Section: Discussionmentioning
confidence: 96%
“…Allergen sensitization Allergen sensitization as reported in Figure 4D was calculated as the percent of allergens (that were tested) with specific sIgE levels (sIgE) R 0.10 kU A /L. Specific sIgE levels were measured for the following allergens: Dermatophagoides pteronyssinus, Dermatophagoides farinae, cat dander, dog dander, mouse, Blatella germanica (cockroach), grass mix, mold yeast mix, tree pollen mix, weed pollen mix (Pham et al, 2019). For the 2 subjects who did not have all ten sIgE levels measured, the percent of the tested allergens that were above the 0.10 threshold are reported in Figure 4D.…”
Section: Clinical Datasetsmentioning
confidence: 99%